Cohesive Properties of Modal Adverbs - Martirossyan, Naira (Armenian Folia Anglistika, 2009)
At the textual level, modal verbs are linked to the preceding, as well as succeeding sentences thereby creating a modaling-evaluative whole which can be viewed as a supraphrasal unity in its type and structure made up of more than one sentence. The components of this whole create different semantic relations with each other including anaphoric (post-positional) and cataphoric (pre-positional) ones. The article attempts to investigate the cohesive properties of modal verbs in monologues and dialogues.